Thermal behavior and rainfall contribution in Lagoa Seca, Brazil between 1981-2019 (Research, Society and Development, 2020)
The thermal oscillations of the air cause direct effects on the production of horticultural products whose economy is based on the municipality of Lagoa Seca. The objective is to analyze the thermal behavior of the period 1981-2019 and its rainfall contributions in the rainy and dry period and its variability in the seasons. The monthly and annual series of precipitation and air temperature for the period (1981-2019) were used in an attempt to understand their climatic fluctuations. The fluctuations in temperatures (maximum, average and minimum) in the autumn and spring seasons have a direct influence on the rainfall rates of the same seasons. The events of maximum and minimum absolute precipitation are related to the maximum and minimum fluctuations of the studied temperatures. These fluctuations of the maximum and absolute minimum of temperature and precipitations must be studied for different regions of the globe, since both the precipitation and the local temperature present high indexes in the rainy period (March to August), followed by the dry period (September to April) that register higher temperatures with some moments of marked reductions.